Mondly language and writing skills: The influence of the Mondly language web media on Arabic writing skills - Lestari, Siti Rizqiyah; Ghufron, Zaki; Indriana, Dina (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to examine the impact of the online learning platform Mondly Language on the Arabic writing skills of seventh-grade students. Writing proficiency is a crucial yet often neglected component of language learning. Adopting a quantitative approach with a quasi-experimental design, the research involved two sample groups: an experimental group using Mondly Language and a control group employing traditional teaching methods. After conducting normality tests, data were collected through pre- and post-tests, leading to the application of a non-parametric statistical analysis using the Mann–Whitney U test. The results showed a statistically significant difference between the two groups (p < 0.05), indicating that the use of Mondly Language positively influences students’ Arabic writing development. Key contributing factors to the effectiveness of the platform include its engaging visual interface, gamification-based interactivity, and varied exercises that promote active student participation in composing Arabic sentences. The findings support the integration of creative, technology-based instructional strategies to enhance Arabic writing skills among junior high school students.